Frequency-Modulated Continuous Wave Radar-Based Through-Wall Human Detection for Emergency Response - Malik, Zainab; Taysi, Ziya Cihan; Karsligil, M. Elif (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2026)
Detecting individuals trapped after earthquakes is critical for guiding rescue operations, yet current search methods still face challenges, especially in large-scale emergencies. This work focuses on leveraging a low-cost, lightweight continuous wave radar (CWR) sensor for through-wall human detection, with the goal of enabling fast, scalable deployment in disaster zones. This solution facilitates deployment across different locations, supporting wide-area coverage, parallel search operations, and rapid rescue in time-critical situations. The proposed system uses machine learning models to accurately detect human presence and classify movement types behind walls, including static, low-energy, and high-energy movements. It achieves 97.1% accuracy in presence detection and 84.5% in static versus movement classification, offering a practical and scalable solution for postdisaster search and rescue.
Keywords: Feature extraction; Accuracy; Radar; Radio frequency; Radar detection; Machine learning; Long short term memory; Sensors; Ultra wideband radar; Frequency-domain analysis; Frequency-modulated continuous wave (FMCW) radar; human detection; through-wall sensing; Computer Science; Engineering